Controlled mechanical loading improves bone regeneration by regulating type H vessels in a S1Pr1‐dependent manner. Issue 10 (5th September 2022) - Yang, Chengyu; Liu, Yang; Wang, Ziyan; Lin, Minmin; Liu, Chao
Abstract: Despite the best treatment, approximately 10% of fractures still face undesirable repair and result in delayed unions or non‐unions. Dynamic mechanical stimulation promotes bone formation, when applied at the correct time frame, with optimal loading magnitude, frequency, and repetition. Controlled mechanical loading significantly increases osteogenic cells during the matrix deposition phase of bone repair. In the bone defect, the blood vessel network guides the initial bone formation activities. A unique blood vessel subtype (Type H) exists in bone, which expresses high levels of CD31 and endomucin, and functions to couple angiogenesis and osteogenesis. However, how this form of controlled mechanical loading regulates the Type H vessels and promotes bone formation is still not clear. Sphingosine 1‐phosphate (S1P) participates in the bone anabolic process and is a key regulator of the blood vessel. Its receptor, sphingosine 1‐phosphate receptor 1 (S1Pr1), is a mechanosensitive protein that regulates vascular integrity. Therefore, we hypothesis that controlled anabolic mechanical loading promotes bone repair by acting on Type H vessels. To study the effect of S1Pr1 on loading induced‐bone repair, we utilized a stabilized tibial defect model, which allows for the application of anabolic mechanical loading. Mechanical loading upregulated S1Pr1 within the entire defect, with up to 80% expressed in blood vessels, as observed by deep tissue imaging. Additionally, S1Pr1 antagonism by W146 inhibited the anabolic effects of mechanical loading. We showed that mechanical loading or activating S1Pr1 could induce YAP nuclear translocation, a key regulator in the cell's mechanical response, in endothelial cells (ECs) in vitro. Inhibition of S1Pr1 in endothelial cells by siRNA reduced loading‐induced YAP nuclear translocation and expressions of angiogenic genes. In vivo, YAP nuclear translocation in Type H vessels was up‐regulated after mechanical loading but was inhibited by antagonizing S1Pr1. S1Pr1 agonist, FTY720, increased bone volume and Type H vessel volume, similar to that of mechanical stimulation. In conclusion, controlled anabolic mechanical loading enhanced bone formation mainly through Type H vessels in a S1Pr1‐dependent manner.